ANALISIS KEBIJAKAN PEMERINTAH KOTA MALANG TERKAIT ANCAMAN PENGANGGURAN PASCA KENAIKAN INFLASI - Vonnylia; Sutjiali, Florensia; Jocelyn, Nathania; Prawira , Johanes; Hendro (Transpublika Publisher, 2023)
One indicator of the cause of inflation is. Inflation and Unemployment have a role in making fiscal and monetary decisions of a country in improving its economic conditions. The purpose of this study is to analyze policies related to the threat of risk after the increase in inflation in the city of Malang. The data processing technique used in this research is qualitative, which is done by collecting the data that is roughly needed. The results revealed that the highest number of expenses in Malang City in 2021 with a total of 63.531, while the lowest number in 2019 with a total of 40.104. The highest amount of inflation in Malang City is in 2014, while the lowest inflation is in 2020. Fiscal policies that can be implemented the government in reducing the levels of movement, namely opening up job opportunities, adding State-Owned Enterprises, and creating job training centers to overcome the impact of inflation the government can make policies; reducing unexpected spending, offering support for 2% of the general allocation fund, increasing tax rates and providing maximum prices for certain goods.